Reading and Rebellion in Catholic Germany, 1770–1914 - Zalar, Jeffrey T. (Publications of the German Historical Institute, 2018)
Interrogates the belief that the clergy defined German Catholic reading habits, showing that readers frequently rebelled against their church's rules